Utilization of Public Relations Communication Media of the Banten Police in Realizing A Safe and Peaceful 2024 Gene-ral Election in the Operation Mantap Brata Program - Vellinda, Bq. Dendha; Annisarizki; Mardiana, Siska (Indonesian Journal of Social Science Research, 2025)
Banten Police Public Relations runs the Mantap Brata Operation program, this program is carried out by the police to ensure security, order, and maintain the smooth running of the election. Banten Police Public Relations provides security and strives so that people can avoid political issues, hoax news, or receive misinformation. The purpose of this study was to determine the utilization of Banten Police Public Relations communication media in realizing a safe and peaceful 2024 General Election in the Operation Mantap Brata program. The method used in this research is a qualitative approach, the results of the study found that the Banten Police Public Relations used many media including social media, mass media, print media, and direct communication to the public to convey messages of a safe and peaceful election campaign and information related to the 2024 Election.